PENGEMBANGAN KEMAMPUAN BERBICARA BAHASA INDONESIA SISWA MELALUI PEMBELAJARAN BEHAVIORISTIK DAN PEMBELAJARAN KOGNITIF - Tita Tanjung Sari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2018)
Human was not given any potential ability in the first time of their existence, but they had consciousness to develop all their potential inside that be a competent and skilled human. The ability that thay had is created by adapting their educational environment. In the curriculum of 2013, teachers are given freedom to facilitate the development of every learner’s ability, including learner’s language ability. This study aims to developing the Indonesian language ability on fifth grade students through behavoristic and cognitive learning. The type of this study is quasi experiments by giving pre-test and post-test. This research was done on fifth grade students on 2017-2018 academic years at a state elementary school, Patean II Sumenep. The data collection methods were in the form of observation, interview, test, and questionnaire. The data was analyzed by simple quantitative description based on the average score of pre-test and post-test. The behaviourism and cognitive lesson significantly affect to the development of students’ language acquisition. During the treatement, the students were experiencing an increase on each indicator. The highest score occurred on the students’ intonation spoken emphasis and the students’ spoken understanding. The students’ intonation spoken emphasis increased by 1,35 of 4 scale. From the 2,1 first average score turns into 3,4, and the students’ spoken understanding competence increased by 1,29 of 4 scale, from the 2,2 first average score and post-test average score of 3,5. The result of this study shows that there is a difference on the students’ Indonesian speaking ability between before and after the treatment.